2021
DOI: 10.2176/nmc.oa.2020-0307
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment for Lateral Wall Paraclinoid Aneurysms and the Influence of Internal Carotid Artery Angle

Abstract: Lateral wall paraclinoid aneurysms (LPA) are a rare type of aneurysm located on the lesser curve side of the internal carotid artery (ICA) bend, at the level of the anterior clinoid process. The objective of this study was to assess the influence of flexion of the ICA on the morphology of aneurysms and outcome of endovascular treatment. Between 2003 and 2018, we treated 643 cases of unruptured paraclinoid aneurysms with endovascular therapy in our institution. Of those cases, aneurysms projecting laterally on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…The wide angle between the two branches accentuates the terminal type of intracranial aneurysm, potentially leading to incomplete occlusion. [20][21][22] Therefore, we did not apply the Enterprise Vascular Reconstruction Device (Codman Neurovascular, Raynham, MA, USA), a widely recognized stent for providing vascular straightening, owing to its longitudinal stiffness. 23)…”
Section: Discussionmentioning
confidence: 99%
“…The wide angle between the two branches accentuates the terminal type of intracranial aneurysm, potentially leading to incomplete occlusion. [20][21][22] Therefore, we did not apply the Enterprise Vascular Reconstruction Device (Codman Neurovascular, Raynham, MA, USA), a widely recognized stent for providing vascular straightening, owing to its longitudinal stiffness. 23)…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from compelling neuroimaging results suggests a relationship between increased carotid siphon tortuosity and paraclinoid aneurysms. Sugiyama et al ( 28 ) compared the carotid siphon to a meandering river in the natural world and reported that meandering rivers experience less erosion on the side with the lesser curve when compared with the side with the greater curve. Also, the riverbed is more easily formed on the side with the lesser curve and it experiences a lower flow velocity.…”
Section: Discussionmentioning
confidence: 99%
“…24 In addition, when we compared dorsal and ventral group aneurysms, statistically significant differences were found in terms of follow-up angiographic outcomes. Sugiyama et al 25 reported that the degree of flexion of the ICA may change the hemodynamic stress and long-term outcomes following embolization of paraclinoid aneurysms. Kim et al 26 showed that paraclinoid aneurysms at different locations had different hemodynamic stress and progressive embolization effect, which may be caused by the curvature and twist of vessels.…”
Section: Discussionmentioning
confidence: 99%